Design Of Interactive Smart Mirror System for Digital Information Display Based on Multitasking Approach Using Raspberry Pi - Nwokoye , Sandra; Aniedu, Azubuike; Okafor, Chukwunenye; Nzemalu, Austine (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2022)
The average time humans look in the mirror is in the early morning when they will get ready for work. A person can rarely focus on other activities such as watching television for the latest news, checking the clock for the correct time, or even checking the weather forecast. Therefore, the purpose of this research is to design an interactive smart mirror that functions as a personal digital assistant to provide a schedule of daily activities, including recognizing the owner's face for access to the smart mirror, displaying weather forecasts, displaying the date and time, as well as the latest news. Unlike most smart mirrors in previous studies, this smart mirror design is connected to a facial recognition system. This will work for such security systems that the user will be granted access to the system only when the system detects that it is the owner. The method used in the research is the agile methodology for the project's flexibility and structured work organization. Experiments will be carried out on all test data starting from the accuracy of turning the smart mirror on and off, loading the weather on average 5 seconds after internet connection, making sure the Pi-camera component is active, and checking for face profiles. The system will test the data on each unit individually and as a whole to ensure efficiency and reliability. The experimental results in this study provide an accurate value of 100%.